Role of Long Chain Fatty Acids in Developmental Programming in Ruminants - José Alejandro Roque-Jiménez; Milca Rosa-Velázquez; Juan Manuel Pinos-Rodríguez; Jorge Genaro Vicente-Martínez; Guillermo Mendoza-Cervantes; Argel Flores-Primo; Héctor Aarón Lee-Rangel; Alejandro E. Relling (Animals, 2021)
Nutrition plays a critical role in developmental programs. These effects can be during gametogenesis, gestation, or early life. Omega-3 polyunsaturated fatty acids (PUFA) are essential for normal physiological functioning and for the health of humans and all domestic species. Recent studies have demonstrated the importance of n-3 PUFA in ruminant diets during gestation and its effects on pre-and postnatal offspring growth and health indices. In addition, different types of fatty acids have different metabolic functions, which affects the developmental program differently depending on when they are supplemented. This review provides a broad perspective of the effect of fatty acid supplementation on the developmental program in ruminants, highlighting the areas of a developmental program that are better known and the areas that more research may be needed.